1997
DOI: 10.1002/(sici)1096-9861(19971110)388:1<64::aid-cne5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of parvalbumin-, calretinin-, and calbindin-D28k-immunoreactive neurons and fibers in the human entorhinal cortex

Abstract: Parvalbumin, calretinin, and calbindin-D28k are calcium-binding proteins that are located in largely nonoverlapping neuronal populations in the brain. The authors studied the distribution of parvalbumin-, calretinin-, and calbindin-D28k-immunoreactive (ir) cells, fibers, terminals, and neuropil in the eight subfields of the human entorhinal cortex. The distribution of each of the three calcium-binding proteins largely followed the cytoarchitectonic borders of the eight entorhinal subfields, although the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
79
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 38 publications
12
79
0
Order By: Relevance
“…2L). Light microscopy analysis showed that the distribution patterns of PVB, CB, and PNNs staining in our tissue correspond well to those detected in the human and monkey amygdala and entorhinal cortex in other laboratories (Hartig et al, 1995;Sorvari et al, 1995Sorvari et al, ,1996bMikkonen et al, 1997). Standard tests for antisera specificity included omission of either the primary or the secondary antisera.…”
supporting
confidence: 76%
“…2L). Light microscopy analysis showed that the distribution patterns of PVB, CB, and PNNs staining in our tissue correspond well to those detected in the human and monkey amygdala and entorhinal cortex in other laboratories (Hartig et al, 1995;Sorvari et al, 1995Sorvari et al, ,1996bMikkonen et al, 1997). Standard tests for antisera specificity included omission of either the primary or the secondary antisera.…”
supporting
confidence: 76%
“…The CB immunoreactivity was observed in pyramidal and non-pyramidal neurons of all areas of the examined structure in chinchilla, similarly as in human (7), macaque (17), and mouse (25). CB-positive reaction was observed in multiform neurons like in human (7), macaque (17), and mouse (25). Weak immunoreactivity was demonstrated in pyramidal shaped cells, and moderate and intensive immunoreactivity in multipolar, bipolar, Cajal-Retzius, as well as in round neurons similarly as in human (7) and macaque (17).…”
Section: Discussionsupporting
confidence: 58%
“…The CB immunoreactivity was observed in pyramidal and non-pyramidal neurons of all areas of the examined structure in chinchilla, similarly as in human (7), macaque (17), and mouse (25). CB-positive reaction was observed in multiform neurons like in human (7), macaque (17), and mouse (25).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations